Isolation of microorganism from oil palm-sap - Muhammad Ridzuan, Kamaruzaman (2011)
Oil palm sap is obtained from squeeze the oil palm trunk. The sap is good medium because rich of nutrients for yeast growth. The objectives of this research are to isolate and identify the yeast species from oil palm sap and determine the growth kinetic of the mix culture of yeast. The isolation of yeast is using streaking method that streak on sabouraud dextrose agar and incubate for 30oC and 48 hours for development yeast colonies on the agar plate. The yeast colonies will re-streak to get pure colonies. The pure colonies are identified by using morphological and biochemical test to determine the species. The growth kinetics are based on Monod kinetics which using cell dried weight and substrate concentration taken every 4 hours until the reading constant or decline. The yeast species in the oil palm sap are Candida spp., Hansenula spp., Fisobasidiella spp., Saccharomyces spp., Pichia spp., Sporobolomyces spp. and Trichosporon spp. The growth kinetics values are 0.0288 (yield coefficient), 0.0058h-1 (decay coefficient), 0.3509h-1 (maximum growth rate) and 1850.711mg/l (half saturation constant). As conclusion, the yeast species can obtain from oil palm sap and can be used for further research.